Christianity Made in India : From Apostle Thomas to Mother Teresa - Hedlund, Roger E. (Minneapolis, MN : Fortress Press, 2017)
Christianity Made in India discusses the indigenization of Christianity in the Indian context, set in the larger context of the exceptional growth of the church in the non-Western world during the twentieth century, which has been characterized by a diversity of localized cultural expressions. It recognizes that the center of Christian influence, numerically and theologically, is shifting southward to Africa, Latin America, and Asia. Increasingly, it is found in nontraditional (non-Catholic, non-Protestant, non-Syrian) churches of indigenous-independent variety, frequently charismatic, not necessarily Pentecostal, but of substantial evangelical and cultural diversity. Predominantly, it is a church of the poor. It affirms the reality that wherever the gospel goes, it takes root in the local culture. - back cover.
Introduction: "beginning from Jerusalem" -- Foundations: Thomas and the first Christians -- A thousand years of silence?: the forgotten golden age of the church -- Ziegenbalg: the beginnings of Protestant Christianity in India -- Carey and the evangelical experiment at Serampore -- Ramabai Dongre Medhavi: change agent in modern Indian history -- Evangelical Christians and social transformation -- Indigenous churches of South Asia and beyond -- Why study new movements?: the importance of India's new Christian movements -- Religious plurality and Christian concerns: insights from India -- Poverty, evangelisation, and Christian identity -- Creative ministries of new Christian movements -- Living water and the Holy Spirit -- Fourth branch Christianity and the historiography of new Christian movements -- Christian identity in a pluralistic world -- Hindus and Christians together for two thousand years -- Conclusion: "To the ends of the earth."
Includes bibliographical references and indexes.
Keywords: Christianity -- India; Christianity -- India; Indian Church History -- Apostle Thomas - Mother Teresa; India -- Church history; Church history